Castor fiber na gruta do Caldeirão Existência, distribuição e extinção do castor em Portugal - Antunes, M. Telles (2010)
Beaver only had been found in Portugal in a Chalcolithic locality, the Vila Nova de S. Pedro castrum. It has now been idenrified in the Upper Paleolithic (Solurrean) from Gruta do Caldeirão, near Tomar. The species has been found recently at «Gruta do Almonda»; 4 teeth were collected in bed C, older than a Solutrean sequence (see Anexo for details). The species seems to have been rare, as it was also the case with portuguese miocene Castoridae Enroxenomys minutus and Chalicomys jaegeri. If account is taken of the presence in the Middle Ages until Castille of words meaning beaver (related to the popular latin Fiber/Biber), it is obvious that these animals still existed then. Such nouns were largely predominant over the rather erudite larin (greek derived) words as Castor, -óris and derived ones, as it could be expected. This allowed us to recognize that veiro should be the corresponding word with Fiber affinities in archaic portuguese. It was previously supposed to mean only expensive furs then imported into Portugal. Indeed it was also a zoonym. Anyway, beaver should be scarce by XIIIth century since it is not included in the quite detailed price list imposed by the «Lei da Almotaçaria» from December 26, 1253 (see Quadro II). Toponyms in veiro and derived words (fig. 2; Quadro III) (plural, feminines, diminutives, inhabited places) give a restrictive view of the Middle Age distribution. Some of them are certainly older than Portugal itself (first half of XIIth century); others existed by the XIVth century but were probably older. Some rare toponyms seem to be derived from rhe erudite latin Castor, -óris. Nothing suggests that these words were still in use as zoonyms during the Middle Ages. All toponyms are located in regions near rivers and other freshwaters ecologically suitable for beavers, so wecan approximately retrace irs former, Middle Age distribution in Portugal (fig. 2; Quadro III). Most of them are located in the Center-West and Northwest of Portugal, with a suitable c1imate (rainfall in general over 800 milimeters per year); the only sure geographical exception is Veiros, in Alto Alentejo province, in a region with comparable precipitations and less dry climare conditions than most of the territories South of the Tagus. There are less and less of these toponyms towards the South and the inner part of the country, and they are enrirely lacking in ali drier regions from Trás-os-Montes, Beira, Alentejo beyond Tagus' basin, and in Algarve. Nothing suggests beavers lived there, No pose-medieval toponym is known, nor any reference after middle XVth century. No such locality was at, or close by to, any frontier. Hence the hypothesis of veiro (e: al.) as meaning but points where expensive furs(supposedly known as veiros in general but without clearly saying from what animal they were obtained from) is to be discarded. During the Middle Ages, beaver distribution concerned all the main river basins from Minho to Tagus ones. Quice racefied in the XIIIth, the beavers may have disappeared from Portugal during the XVth century. Ecological requirements restricted their former distribution. Vulnerability to natural causes (i.e., severe drought) and to human pressure may have accounted heavily for this species extinction. Last (1446) reference for Portugal known to us suggests the species was by then almost extinct.